1996
DOI: 10.1021/ic950738v
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Ethylene Oligomerization by an Organometallic Nickel Catalyst

Abstract: The mechanism for ethylene oligomerization by (acac)NiH has been studied using density functional theory (DFT). The transition states for chain propagation and chain termination were optimized and the related reaction barriers calculated. Several possible mechanisms were considered for the chain termination step. Chain termination by beta-hydrogen elimination was found to be energetically unfavorable, and is not likely to be important. Instead, beta-hydrogen transfer to the incoming ethylene unit seems to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 21 publications
(18 reference statements)
4
31
0
Order By: Relevance
“…However, based on DFT calculations, Fan et al [45] concluded that Ni-H regeneration through β-hydride elimination is energetically unfavorable.…”
Section: Semk Model Construction 41 Proposed Mechanism For Ethene Olmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on DFT calculations, Fan et al [45] concluded that Ni-H regeneration through β-hydride elimination is energetically unfavorable.…”
Section: Semk Model Construction 41 Proposed Mechanism For Ethene Olmentioning
confidence: 99%
“…An early transition state was assumed making the transition state to resemble the corresponding reactant [45].…”
Section: Determination Of the Number Of Single-eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…From IMI-2 to IMF-1, although we could not locate the transition state for this process despite detailed investigations of the potential energy surface of Pt-H β bond broken down, the barrier can be estimated to be over 75.31 kJ/mol according to the β-agostic interaction in IMI-2. 34 By comparison, the barrier of IMI-1→IMI-2 is higher in energy than that of IMH-1→IMH-2(IMF). Therefore, the pathway I is more favored.…”
Section: Catalytic Cycle For Ethylene Dimerizationmentioning
confidence: 96%
“…The growth in the selectivity towards hexenes can be attributed to the co-oligomerization of the primary products, butenes, with ethylene. Increasing the temperature increases both the formation of C4 and the formation of co-oligomerization products [31].…”
Section: Ethylene Oligomerization With Ironmentioning
confidence: 99%